pengaruh gaya kepemimpinan, komunikasi dan motivasi terhadap kepuasan kerja karyawan cv. chandra motorsport - Muhamad Agus; Hadiyatno, Didik; .Yuliani, Ttutik (MEDIA RISET EKONOMI [MR.EKO], 2024)
This research aims to determine the influence of leadership style, communication and motivation on employee job satisfaction at CV. Chandra Motorsport. The sampling technique in this research was total sampling with a population of 35 CV employees. Chandra Motorsport. The data collection method was carried out by distributing questionnaires. This research uses SmartPLS to manage data. The results of this research indicate that the Leadership Style variable has a positive and significant effect on Employee Job Satisfaction at CV. Chandra Motorsport. The Communication variable has a positive and significant effect on CV Employee Job Satisfaction. Chandra Motorsport. The motivation variable has a positive and significant effect on CV employee job satisfaction. Chandra Motorsport. The first hypothesis tests whether the Leadership Style variable (X1) has a significant positive effect on the Job Satisfaction variable (Y). The test results show a p-value of 0.002 or smaller than 0.05. And has a t statistical value of 3,050 (t statistic > t table 1.96). This proves that the Leadership Style variable(X¬1) has a significant positive influence on the Job Satisfaction variable (Y) so that the first hypothesis can be accepted.The second hypothesis tests whether the Communication variable (X2) has an effect on the Job Satisfaction variable (Y). The test results show a p-value of 0.004 or smaller than 0.05. And has a t statistical value of 2,913 (t statistic > t table 1.96). This proves that the Communication variable has an influence on Job Satisfaction (Y) so it can be concluded that the second hypothesis can be accepted.The third hypothesis tests whether the Motivation variable (X3) has an effect on the Job Satisfaction variable (Y). The test results show a p-value of 0.000 or smaller than 0.05. And has a t statistical value of 4,573 (t statistic > t table 1.96). This proves that the Motivation variable has an influence on Job Satisfaction (Y) so it can be concluded that the third hypothesis can be accepted. Based on the results of research analysis that has been carried out regarding the influence of leadership style, communication and motivation on employee job satisfaction at CV. Chandra Motorsport can draw the following conclusions: Based on the test results, the leadership style variable has a positive and significant effect on employee job satisfaction. Based on the test results, the communication variable has a positive and significant effect on employee job satisfaction. Based on the test results, motivation has a significant positive effect on employee job satisfaction.